MENINGKATKAN KEMAMPUAN REPRESENTASI DAN DISPOSISI MATEMATIS SISWA MELALUI MODEL PEMBELAJARAN COOVERATIVE PROBLEM SOLVING - Saputra, Tatang; Sugiatno, Sugiatno; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed at analizing the ability of the students? mathematics representation on linear program materials after analizing the students? mathematics disposition and having cooperative problem solving model. This research was qualitative research with quantitative data as a tool to describe the students? achievement result. The research subject was the 8 students based on the lowest pre test result from the students of XI MIPA2.The research was conducted for once meeting. The delivering of lesson materials used cooperative problem solving model to the students with pedagogic treatment in the form of micro didactic. The observer who was from the mathematics education background of knowledge also stayed in class during the learning process. The data which had been collected were the implementation of cooperative problem solving, the students? learning activity, the students? ability on mathematics representation and disposition. Based on the research result, it could be concluded that cooperative problem solving model could increase the students?ability on mathematics representation and disposition. This could be proved by the increasing things as follow: First, the 8 students?ability on mathematics representation which was from the pre test average score 44,00 became 77,43 on post test. The total students who achieved the passing grade were 0 student from 8 students (0%) became 6 students from 8 students (75%) who completely passed the passing grade. Second, the students?ability on mathematics disposition was considered good/high. The average score increased from 54,50 (68,13%) became 61,00 (72,19%).Key Words            :  The Ability on Mathematics Representation, The students                           Mathematics Disposition and Cooperative Problem Solving Model